PTU-047 Biodegradable Oesophageal Stents In Benign And Malignant Disease – A Single Centre Experience. (9th June 2014) - Siddhi, SS; Plevris, J; Bow, S
Abstract : Introduction: Biodegradable oesophageal stents have been developed recently and the experience in their use and available literature in limited. Their usefulness has been demonstrated in refractory benign strictures in a handful of studies and their role in malignant strictures is relatively untested. We looked at our practice and the clinical outcomes in the use of these stents. Methods: This is a retrospective observational study looking at electronic case record and endoscopy reports. All patients who had biodegradable stents inserted between March 2011 and September 2013 were included for analysis. Twenty-three stents were inserted in 16 patients. 5 of these patients had 2 stents and one patient had 3 stents over the period of time. Thirteen stents were inserted for benign disease and eight for malignant strictures. There were 9 males and 7 females with age range being between 47 yrs and 101 yrs 2 stents were inserted in 1 patient with postoperative tracheo-oesophageal fistula. Results: In the benign group, an average of 10.5 endoscopies (0.95/month/patient) and 7.2 dilatations (0.65/month/patient) were necessary prior to stent insertion per patient. Post insertion there was a reduction to 3.5 endoscopies (0.03/month/patient) and 2 dilatations (0.016/month/patient). When the average number of dilatations was analysed pre and post stent insertions per patient per month, there was a significant reduction with a P value of 0.009 on the paired T test. In the benign group, on an average 7 endoscopies and 5 dilatations were avoided/patient. Interval between dilatations increased from 5.2 to 25 weeks. In the malignant group, all patients were successfully bridged to chemo/radiotherapy. 2 out 6 patients went on to metal stents after 3 and 5 months due to disease progression. The stent insertion was technically successful in all cases following a dilatation of the stricture to 12mm at the time of insertion. Four patients complained of some pain post stent insertion (3 in the malignant group and 1 in the benign group). One patient developed sepsis post procedure but recovered well with a course of antibiotics. No other complications were noted. In all cases where a check up endoscopy was done, the stent had disintegrated within 8–12 weeks. Conclusion: BD stents are of value in recurrent benign oesophageal strictures as they reduced the number and frequency of dilatations. The BD stents successfully bridge patients with malignant strictures to oncological therapies. Insertion of a BD stent does not preclude a later insertion of a permanent metal stent. Stent insertion was technically successful and safe. Disclosure of Interest: None Declared.